Numerical simulation of magnetic field for electromagnetic casting of hollow billets - Wang,Z. F. (2005)
Distribution of magnetic field during electromagnetic continuous casting of hollow billets of aluminum alloys is studied by the method of numerical simulation. Two-dimensional axis-symmetric finite element model including water-cooled core, outer mould, ingot, inner and outer induction coil has been established. Distribution of magnetic flux density is obtained by solving magnetic vector potential formulations. 1) In electromagnetic casting, inner and outer induction coil interact, magnitude and admeasurements of current affect directly distribution of magnetic flux density. 2) Magnetic flux density near interior surface of pipe wall is increased notablely by increasing appropriately frequency. 3) Phase difference affects the magnitude and direction of the gradient of magnetic flux density.